2007
DOI: 10.1002/jmv.20904
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genotype 4 hepatitis E virus strains from a patient with acute hepatitis E and farm pigs in Bali, Indonesia

Abstract: A previous study revealed that antibodies to hepatitis E virus (HEV) (anti-HEV) are highly prevalent among healthy individuals and farm pigs in Bali, Indonesia, and suggested that HEV infection may occur via zoonosis among Balinese people. However, there were no reports of acute hepatitis E in Bali. To elucidate whether Balinese HEV strains recovered from infected humans and pigs have significant sequence similarity, serum samples obtained from 57 patients (age, mean +/- standard deviation, 31.1 +/- 11.9 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 60 publications
1
15
0
Order By: Relevance
“…[5][6][7][8][16][17][18][19] Moreover, there are many published articles about zoonotic transmission of HEV from wild boar to humans in rural area as well as urban regions. 20,21 Therefore, hepatitis E should be tested in patients with unexplained hepatitis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…[5][6][7][8][16][17][18][19] Moreover, there are many published articles about zoonotic transmission of HEV from wild boar to humans in rural area as well as urban regions. 20,21 Therefore, hepatitis E should be tested in patients with unexplained hepatitis.…”
Section: Discussionmentioning
confidence: 98%
“…Sporadic cases of genotype 3 or 4 acute hepatitis E have recently been reported in several developed countries such as France, Germany and Japan. [5][6][7][8]16,17 One report from Bali, Indonesia showed the nucleotide sequence homology of genotype 4 HEV within person and animal (pigs), 18 and the nucleotide sequence homology between 2010-BSNU-AYC with BaliE03-46(AB298178), was about 86%.…”
Section: Similar and Contrasting Cases In The Literaturementioning
confidence: 98%
“…The HEV molecular epidemiology has been found to be complex in this country, as several HEV-4 subtypes, including subtypes b and d, have been detected, and sequences recovered from humans were found (although inconsistently) to share a high level of nucleotide similarity with those found from swine in the same geographical area [19,20,22]. Otherwise, HEV-4 have been collected in India, Indonesia, South Korea, Taiwan and Vietnam [18,20,23,24,25,26,27], including in autochthonous hepatitis E, and an epidemiological link with pigs or wild boars has been observed in cases diagnosed in Bali and South Korea [14,23,25]. In addition, HEV-4 infection was reported in 2010 in England in a patient who returned from a 2-month stay in India 1 month before presenting jaundice [28].…”
Section: Figmentioning
confidence: 99%
“…The fi rst animal in which HEV genotype 3 was identifi ed and characterized was pig in the United States (6). HEV strains of genotypes 3 and 4 have since been detected in pigs in many other countries, and these strains were found to be genetically closely related to HEV strains originating from humans in the same geographic region (7,8). Serologic studies have also indicated a broad host range of HEV.…”
mentioning
confidence: 99%